Is the Cu/Zn Disorder the Main Culprit for the Voltage Deficit in Kesterite Solar Cells?. Issue 12 (29th March 2016) - Bourdais, Stéphane; Choné, Christophe; Delatouche, Bruno; Jacob, Alain; Larramona, Gerardo; Moisan, Camille; Lafond, Alain; Donatini, Fabrice; Rey, Germain; Siebentritt, Susanne; Walsh, Aron; Dennler, Gilles
Abstract : Photovoltaic thin film solar cells based on kesterite Cu2 ZnSn(Sx, Se1–x )4 compounds (CZTSSe) have reached >12% sunlight‐to‐electricity conversion efficiency. This is still far from the >20% record devices known in Cu(In1–y, Gay )Se2 and CdTe parent technologies. A selection of >9% CZTSSe devices reported in the literature is examined to review the progress achieved over the past few years. These devices suffer from a low open‐circuit voltage ( V oc ) never better than 60% of the V oc max, which is expected from the Shockley‐Queisser radiative limit (S‐Q limit). The possible role of anionic (S/Se) distribution and of cationic (Cu/Zn) disorder on the V oc deficit and on the ultimate photovoltaic performance of kesterite devices, are clarified here. While the S/Se anionic distribution is expected to be homogeneous for any ratio x, some grain‐to‐grain and other non‐uniformity over larger area can be found, as quantified on our CZTSSe films. Nevertheless, these anionic distributions can be considered to have a negligible impact on the V oc deficit. On the Cu/Zn order side, even though significant bandgap changes (>10%) can be observed, a similar conclusion is brought from experimental devices and from calculations, still within the radiative S‐Q limit. The implications and future ways for improvement are discussed. Abstract : The possible role of the cationic (Cu/Zn) disorder and anionic (S/Se) distribution on the severe Voc deficit generally reported in CZTSSe‐based solar cells is investigated. It is concluded that none of these disorders is likely to be the direct main culprit for the Voc deficit, but that the partially‐ordered state is preferred as it promotes radiative recombination.